Integrating Infection Control into Public Health Systems: A Global Review of Surveillance, Prevention Programs, and Interventions for Mitigating Epidemic and Pandemic Risks - Alla Eid Alraddadi; Fahd Saeed Alyami; ‎‏Almuhannad Hamdan Salh Alyahiwi; Mansour Dhaifallah Ahmed Muharraq; Ahmed Asaad Ahmed Ghazwani; Saleh Ali Alyami; Hussam Khaled Albouji (International Journal of Medical Toxicology and Legal Medicine, 2025)
The integration of infection control measures within public health systems has become increasingly essential in light of recurrent global epidemics and pandemics. The COVID-19 crisis, in particular, exposed significant gaps in the preparedness and responsiveness of healthcare infrastructures worldwide. This review critically examines the intersection of infection control and public health by synthesizing global evidence on surveillance mechanisms, prevention programs, and targeted interventions aimed at reducing the risks of epidemic and pandemic outbreaks. Drawing on international frameworks such as the International Health Regulations and the One Health approach, the paper highlights the role of surveillance technologies, vaccination initiatives, non-pharmaceutical interventions, and community engagement in enhancing health security. The review also identifies persistent challenges, including disparities in resource allocation, policy fragmentation, and public mistrust, which hinder effective integration. It emphasizes the need for cohesive strategies that unify infection control practices with public health policies to build resilient health systems capable of mitigating future biological threats. The findings offer valuable insights for policymakers, healthcare practitioners, and researchers seeking to reinforce global health defenses through a more integrated approach to infection prevention and control.